Different Jargon Language Variations Bonek Mania Ball Supporter and The Jak Mania (Sociolinguistic Studies) - Malik Fahad; Mashud (Universitas Negeri Semarang, 2024)
Bonek Mania and the Jak Mania are two very fanatical football supporter communities in Indonesia. They have different variations of jargon that reflect the identity of the community. Several factors influence the variations in jargon language. This research aims to describe the jargon of Bonek Mania and the Jak Mania football supporters, including analyzing the forms, meanings, and function of its uses and the factors of jargon differences between them. In this study, researchers used a qualitative descriptive method. The data collected by the researchers consists of words or terms in units of words, phrases, sentences, and acronyms. The collection of jargon is obtained from communication between football supporters Bok Mania and Jak Mania on social media comments on Instagram posts, @officialpersebaya account, and @persija account, and when researchers tribunal directly at the stadium. The results of this study indicate that the jargon used by Bok Mania and the Jak Mania supporters both tend to function to encourage and criticize their respective teams. In terms of form, the jargon used by Bonek Mania supporters combines Javanese and Arabic, although there is also English. Meanwhile, the jargon used by the Jak Mania supporters tends to combine Indonesian and English. Several factors influence these differences, including social and environmental factors, regional language, club logos and nicknames, and local cultural culture. This research can be used as a reference for the general public who wants to know the purpose, function, and factors behind the variations in the jargon of bonek mania and the jak mania.